Total Flavonoids from Carya cathayensis Sarg. Leaves Alleviate H9c2 Cells Hypoxia/Reoxygenation Injury via Effects on miR-21 Expression, PTEN/Akt, and the Bcl-2/Bax Pathway. (5th December 2018) - Jiang, Ruibin; Guo, Yan; Chen, Nipi; Gao, Chengxian; Ding, Zhishan; Jin, Bo
Abstract : This study aimed to investigate whether the total flavonoids (TFs) from Carya cathayensis Sarg. leaves alleviate hypoxia/reoxygenation (H/R) injury in H9c2 cardiomyocytes and to explore potential mechanisms. H9c2 cells pretreated with TFs for 24h were exposed to H/R treatment. The results indicated that TFs significantly alleviate H/R injury, which include inhibiting apoptosis and enhancing antioxidant capacity. The protective effects of TFs resulted in higher expression of miR-21 in H/R-induced H9c2 cells than that of controls, which in turn upregulated Akt signaling activity via suppressing the expression of PTEN together with decreasing the ratio of Bax/Bcl-2, caspase3, and cleaved-caspase3 expression in H/R-induced H9c2 cells. Conversely, blocking miR-21 expression with miR-21 inhibitor effectively suppressed the protective effects of TFs against H/R-induced injury. Our study suggests that TFs can decrease cell apoptosis, which may be mediated by altering the expression of miR-21, PTEN/Akt, and Bcl/Bax.